“El divorcio en sede notarial, requisitos previos y sus incidencias ante la concurrencia de hijos comunes menores de edad.” - Paz Moncayo, Iván Darío (2021)
This thesis entitled: "DIVORCE AT A NOTARIAL SEAT, PRIOR REQUIREMENTS AND ITS INCIDENTS BEFORE THE CONCURRENCE OF COMMON CHILDREN UNDER AGE", refers to a process of recent appearance, such as divorce under the attribution that a notary has to be able to resolve such act in its jurisdiction, through the use of various requirements whereby a couple of spouses resolves to terminate the marriage bond that unites them. Being a procedure of recent appearance, it is not generally known to society in general, in the Ecuadorian legal framework, many of the times citizens are unaware of the application of these rights that they can avail themselves of. Currently, it is an extremely agile and easy procedure to obtain, in the case of fulfilling basic requirements prior to the achievement of this act, basic such as the presentation of identity documents, marriage certificate and it is where we focus our investigation, in the case of There are minor children, the agreement by means of a mediation act where the possession, visits and food related to the minor or minors who are involved in the divorce are determined. According to the Ecuadorian legislation in the Notarial Law, specifically in article 18, numeral 22, it is admitted for processing once they have made and obtained such requirements, which will lead to the divorce deed being carried out. The minor, which includes people under 18 years of age, who due to their capacity have not developed optimally, since cognitively they do not reach the necessary maturity to be able to perform various acts, is where the need arises for them to be represented by A person of legal age. This research was developed based on a conceptual, doctrinal and legal study with national and international regulations, as well as through different methods such as surveys, interviews and case studies, which finally allowed proposing a legal reform to the Notarial Law, on the grounds that the incorporation of a prerequisite is amended as a prerequisite, such as the judicial pronouncement of a competent judge in cases of divorce in notarial offices.